2018
DOI: 10.1007/s00208-018-1693-9
|View full text |Cite
|
Sign up to set email alerts
|

Hölder estimates for homotopy operators on strictly pseudoconvex domains with $$C^2$$ C 2 boundary

Abstract: We derive a new homotopy formula for a strictly pseudoconvex domain of C 2 boundary in C n by using a method of Lieb and Range and obtain estimates in Lipschitz spaces for the homotopy operators. For r > 1 and q > 0, we obtain a r +1/2 solution u to ∂u = f for a ∂-closed (0, q)-form f of class r in the domain. We apply the estimates to obtain boundary regularities of D-solutions for a domain inthat admits a derivative estimate. Here ϕ is a (0, q)-form in D and ϕ, ∂ϕ are in C 1 (D). We will prove the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…We also prove an analogous result when ϕ is in Hölder-Zygmund space Λ r (Ω) which improves an earlier theorem of Gong [Gon19].…”
supporting
confidence: 76%
See 2 more Smart Citations
“…We also prove an analogous result when ϕ is in Hölder-Zygmund space Λ r (Ω) which improves an earlier theorem of Gong [Gon19].…”
supporting
confidence: 76%
“…Together with the commutator estimate and Hardy-Littlewood lemma, this leads to the proof of Theorem 1.1. Unlike in [Gon19] and [Shi21], no integration by parts is used in our proof.…”
Section: Sobolev Estimates Of Homotopy Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the boundary is only finitely smooth, we need the following regularized Henkin-Ramirez function constructed by Gong [Gon19].…”
Section: Sobolev Estimates Of Homotopy Operatorsmentioning
confidence: 99%
“…More recently, Gong [Gon19] constructed a ∂ solution operator on strictly pseudoconvex domains with C 2 boundary which gains 1/2 derivative for any ϕ ∈ Λ r (Ω), r > 1. Assuming C 2 boundary still, the authors in a recent preprint [SY21b] found a ∂ solution operator which gains 1/2 derivative for any ϕ ∈ H s,p (Ω), with 1 < p < ∞ and s > 1 p ; it was further shown in [SY21b] that the same solution operator gains 1/2 derivative for any ϕ ∈ Λ r (Ω), r > 0.…”
Section: Introductionmentioning
confidence: 99%